Case study: Multifocal atrial tachycardia during cataract surgery: to operate or not to operate - Jesús Nieves-Alonso; Rosa Méndez Hernández; Fernando Ramasco Rueda (Academia Medicine)
Background: Multifocal atrial tachycardia (MAT) is an uncommon supraventricular arrhythmia that can be seen most commonly in elderly patients with underlying lung disease. It can be easily misinterpreted as atrial fibrillation. Case presentation: We identified an episode of MAT in an asymptomatic patient who was scheduled for ambulatory cataract surgery. After a detailed physical examination and focused cardiac ultrasound (FoCUS), we decided to proceed with the surgery. Conclusions: When MAT occurs in the preoperative period, it can be challenging to decide whether to proceed with the surgical procedure or to perform prior evaluation by a cardiologist. Anamnesis, physical examination, and FoCUS are useful tools in making this decision.